Dysfunkcja słuchu nie jest przeszkodą w uczeniu się języka obcego - Skowronek, Barbara (Scripta Neophilologica Posnaniensia, 2022)
A human being communicates with the help of all his/her senses (especially hearing, sight, touch) and language. Hearing dysfunction makes it difficult to perceive reality, prevents, or at least seriously hinders, communication. Learning your first (native) language is not easy, but possible; with the help of inclusive learning it is also possible to learn a foreign language.